Investigation of the Anti-diabetic and Anti-lipid Peroxidative Properties of Gallic Acid in Diabetic Rats - Mitra Arman; Mostafa Alinaghizadeh; Mahmoud Kordi; Saeid Tamadoni Jahromi; Hanif Amrulloh; Hamed Kioumarsi (Pandawa Institute, 2025)
Diabetes mellitus is a chronic non-communicable disease that occurs due to insulin deficiency or reduced function in the body. Therefore, the scientific investigation of herbal plants and their effectiveness is essential. It has been shown that gallic acid has hypoglycemic properties. In this study, the anti-diabetic and anti-lipid peroxidation properties of gallic acid were investigated. For this purpose, Streptozotocin was injected intraperitoneally into male rats at a dose of 60 mg/kg to induce type I diabetes. Seven days after Streptozotocin injection, blood samples were taken and rats with serum glucose levels higher than 250 mg/dL were considered diabetic. The rats were divided into 4 groups. Two groups of diabetic rats received either water or gallic acid at a dose of 40 mg/kg, and two groups of normal rats received either water or gallic acid at 40 mg/kg dose. The treatment period for all groups was 8 weeks. After the end of the period, blood samples were taken from the rats under fasting conditions. The collected blood samples were analyzed for serum biochemical factors (glucose, cholesterol, triglycerides, High-density lipoprotein, and creatinine) using spectrophotometry with the respective kits, and the level of lipid peroxidation in red blood cells was measured. The administration of gallic acid at a dose of 40 mg/kg (8 weeks) significantly reduced serum levels of glucose, triglycerides, cholesterol, alanine aminotransferase, aspartate aminotransferase, very low-density lipoprotein, low-density lipoprotein, and creatinine, while significantly increasing serum levels of high-density lipoprotein. Additionally, the level of Malondialdehyde in red blood cells was decreased in the diabetic group receiving gallic acid compared to the diabetic control group, and in normal rats receiving gallic acid at a dose of 40 mg/kg (8 weeks), it had no significant effect on serum factors and had no toxicity.